(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article indicates the monetary policy instruments developed over the years under the influence of innovative ideas based on the best practices of developed countries, and examines the scientific and theoretical views of foreign economists in this regard. It is also based on the fact that monetary policy has played an important role in solving financial and economic crises, epidemics, pandemics, macroeconomic and financial problems observed at different periods in the history of world economies. Also, the influence of monetary policy instruments on the supply and demand of money in the economy is analyzed. In particular, the change in the refinancing rate on the growth rate of monetary aggregates in Uzbekistan based on practical data from the official website of the Central Bank of the Republic of Uzbekistan. The practice of using monetary policy instruments in Uzbekistan is analyzed, existing problems are identified and their scientific solutions are presented. In turn, science-based scientific, theoretical and practical proposals and recommendations have been developed to increase the role of Uzbekistan in strengthening sustainable economic growth, financial and macroeconomic stability by improving monetary policy.